log(2x+6)144=2

Simple and best practice solution for log(2x+6)144=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(2x+6)144=2 equation:


Simplifying
log(2x + 6) * 144 = 2

Reorder the terms:
glo(6 + 2x) * 144 = 2

Reorder the terms for easier multiplication:
144glo(6 + 2x) = 2
(6 * 144glo + 2x * 144glo) = 2
(864glo + 288glox) = 2

Solving
864glo + 288glox = 2

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Reorder the terms:
-2 + 864glo + 288glox = 2 + -2

Combine like terms: 2 + -2 = 0
-2 + 864glo + 288glox = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-1 + 432glo + 144glox) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-1 + 432glo + 144glox)' equal to zero and attempt to solve: Simplifying -1 + 432glo + 144glox = 0 Solving -1 + 432glo + 144glox = 0 Move all terms containing g to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 432glo + 1 + 144glox = 0 + 1 Reorder the terms: -1 + 1 + 432glo + 144glox = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 432glo + 144glox = 0 + 1 432glo + 144glox = 0 + 1 Combine like terms: 0 + 1 = 1 432glo + 144glox = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 4x+8+3x-5=129 | | 6(4-x)+7y=23 | | x^3+2x+8=0 | | x-3(9+x)=-11 | | x-3(9+x)=-11 | | 2(2x+3)-4(2-3x)=6+x | | 14-2(3p+p)=6(4+p) | | 5(2x+8)=7x+20 | | 0.05x+0.04y=420 | | -7-2x=-19 | | -1(3z+4)=6z+-3(3z+2) | | 3(2x+4)-x=11 | | f(x)=3x^2+6x-7 | | 5c-4(9-c)= | | 5c+4c= | | 3(2x+5)-x=11 | | 5c+4n= | | [x-3]=12 | | z+30=16 | | 14+3n=8n-3(1n-4) | | 17=2x+3 | | 4(2x+1)=x+4 | | 18-10(x-1)=4x | | 2-4/2 | | 1/3(5y-1) | | 8+f(4/5)=0 | | -8x-(3x+6)=4-1x | | 5x-4=1-x | | (y^2-4y+3)/(5y^2-40y+35) | | 4y-3(2y-7)=5y+12 | | v^2-v=30 | | x-5+3x/4=-5+7x/4 |

Equations solver categories